Comparing Aimed Movements in the Real World and in Virtual Reality - Liu, Lei; van Liere, Robert; Nieuwenhuizen, Catharina; Martens, Jean-Bernard (2009 IEEE Virtual Reality Conference, 2009)
The study of aimed movements has a long history, starting at least as far back as 1899 when Wood-worth proposed a two-component model in which aimed movements are broken into an initial ballistic phase and an additional control phase. In this paper, we use Wood-worth's model for experimentally comparing aimed movements in the real world with those in a virtual environment. Trajectories from real world movements have been collected and compared to trajectories of movements taken from a virtual environment. From this, we show that significant temporal differences arise in both the ballistic and control phases, but the difference is much larger in the control phase; users' improvement is relatively greater in the virtual world than in the real world. They progress more in ballistic phase in the real world, but more in correction phase in the virtual world. These results allow us to better understand the pointing tasks in virtual environments.